Distance education : statewide, institutional, and international applications : readings from the pages of Distance Learning Journal - Simonson, Michael R. (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
This book is a collection of readings from Distance Learning journal written by practitioners for practitioners.
Keywords: Distance education.; Education -- Distance, Open & Online Education.; Open learning, distance education.; elektronické knihy; electronic books